2023
DOI: 10.1021/jacs.3c01666
|View full text |Cite
|
Sign up to set email alerts
|

Self-Immolative Photosensitizers for Self-Reported Cancer Phototheranostics

Abstract: Photosensitizers to precise target and change fluorescence upon light illumination could accurately self-report where and when the photosensitizers work, enabling us to visualize the therapeutic process and precisely regulate treatment outcomes, which is the unremitting pursuit of precision and personalized medicine. Here, we report self-immolative photosensitizers by adopting a strategy of light-manipulated oxidative cleavage of CC bonds that can generate a burst of reactive oxygen species, to cleave to rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…2d, S19 and S21†), the production of ROS in living cells was investigated using 2, 7-dichlorodihydrofluorescein diacetate (DCFH-DA) as a ROS indicator and DHE as an O 2 ˙ − indicator. 14,39 As can be seen in Fig. 6, in all cases the cells exhibited strong fluorescence signals corresponding to ROS and O 2 ˙ − production in the presence of ZZ-NN and ZZ-EDA with photo-irradiation (800 nm, 9.15 mW cm −2 , 3.0 min).…”
Section: Resultsmentioning
confidence: 61%
“…2d, S19 and S21†), the production of ROS in living cells was investigated using 2, 7-dichlorodihydrofluorescein diacetate (DCFH-DA) as a ROS indicator and DHE as an O 2 ˙ − indicator. 14,39 As can be seen in Fig. 6, in all cases the cells exhibited strong fluorescence signals corresponding to ROS and O 2 ˙ − production in the presence of ZZ-NN and ZZ-EDA with photo-irradiation (800 nm, 9.15 mW cm −2 , 3.0 min).…”
Section: Resultsmentioning
confidence: 61%
“…188 Wang et al reported a photosensitizer called NG-cRGD, which consisted of a cyclic pentapeptide (cRGD) that specifically targeted integrin avb3 in tumors, and a 2-cyano-4nitrobenzene-1-sulfonyl group that was responsive to glutathione. 189 NG-cRGD incorporated a strong electronabsorbing group that effectively inhibited the breaking of CQC bonds and the associated phototoxicity. This led to the temporary inactivation and fluorescence burst of the photosensitizer.…”
Section: Pdtmentioning
confidence: 99%
“…1–3 Most photosensitizers (PSs), in clinical and preclinical settings, generate singlet oxygen ( 1 O 2 ) via the type II mechanism, which involves energy transfer between the excited triplet state ( 3 PS*) and O 2 . 4,5 Because of the abnormal proliferation of cancer cells, the limited O 2 supply severely hinders the efficacy of these PSs for PDT. 6–8 Distinguished from type II PSs, the type I PSs produce reactive oxygen species (ROS), 9–11 such as superoxide (O 2 ˙ − ), 12–18 hydroxyl radical (˙OH), 19 and hydrogen peroxide (H 2 O 2 ), 20,21 through an electron or hydrogen proton transfer process, with ˙OH being the most reactive.…”
Section: Introductionmentioning
confidence: 99%